Ionic Liquids as “Green Solvents”: Are they Safe? - Veloso, Gabriela Brasil Romão; Andrade, Rebecca S.; Cicarelli, Regina Maria Barretto [UNESP]; Iglesias, Miguel; Chiari-Andréo, Bruna Galdorfini (Springer Nature, 2020)
Ionic liquids or molten salts are organic salts in a liquid state under normalized conditions, composed by organic cations and inorganic or organic anions. Although they represent a wide diversity of industrial applications, several physicochemical properties and sustainable profile and are usually referred to as “green solvents”, nevertheless, the issues regarding their toxicity to the environment and to humans are still scarce. Considering the importance of the ionic liquids in the industrial area as well as the lack of information about their potential toxicity, this chapter aimed to further investigate the toxicological aspects of ionic liquids, mainly their impacts on human health, based on scientific data recently reported. Literature analysis had shown few studies on ionic liquids targeting human toxicity and also that their toxic effect is directly dependent on the nature of the chemical structure, and in some cases may be more toxic than conventional solvents. However, due to the versatile cations and anions combinations of the ionic liquids, a number of biocomposites can be synthesized and even be used with safe in industries, such as biotechnology, cosmetic, pharmaceutical, textile. Here we reinforce the need to study the toxicological aspects of ILs, mainly in relation to its safety for humans.
Keywords: Aprotic ionic liquids; Cytotoxicity; Ecotoxicity; Green chemistry; Green solvents; Ionic liquids; Protic ionic liquids; Safety; Sustainable industrial processes; Toxicity